RANCANG BANGUN WELD POINT SEBAGAI ALAT PERBAIKAN BODI KENDARAAN BERMOTOR: RANCANG BANGUN WELD POINT SEBAGAI ALAT PERBAIKAN BODI KENDARAAN BERMOTOR - Fawzi, Ahmad Bahar; Utama, Firman Yasa (Jurnal Rekayasa Mesin, 2020)
Abstract The development of the body of the vehicle holds an important roleinthe eficiency of the vehicle. One of them is Speed vehicle which is affected by the stability of the vehicle, the shape and surface of the vehicle body Currently the number of passenger cars in Indonesia in 2018 has reached 16,440,987 units (Central Bureau of Statistics, 2020). The rapid increase in the number of car ownership is offset by the high number of car accidents mainly because the driver or owner of the car has not mastered the condition or performance of the vehicle. The number of car accidents has an impact on the type of damage inflicted both mild, moderate, and severe damage. Damage to the body of the car certainly needs repair to look good kembali. There fore the Weld point tool is designed to facilitate the process of repairing the body of a motor vehicle. The purpose of this tool is to repair the body of the motor vehicle.The benefit of this weld point tool is to facilitate the process of repairing the body of the vehicle with out perforating the plate and minimize the reduced quality of the repaired plate. Methods range from observation, determining problem limitations, tool creation execution, testing, to data retrieval. The Weld point tool uses a 10 ampere travo with a voltage of 10-24 volts and is equipped with a controller timer switch. The result of analisa tool, platcan be kembali as original and the ring is still attached (successfully) when using 10 rings with a time of 5 seconds and a strong current of 24 volts. So it can be concluded that on transformer modification of the former microwafe and its primary twists using email wire EIW diameter 2.5 mm can produce a maximum voltage of 24 volts. Dent pulling can stick well to a plate size of 0.6 mm using a voltage of 24 volts at a time of 5 seconds. The current strength and voltage of the Weld point tool can be adjusted with the controller on the controller timer switch, so that the ampere can be adjusted by increasing or reducing the voltage and time. Keywords: Vehicle Body Repair, Weld point, Current Strength, Voltage.